Pengaruh Pendidikan Etika Bisnis, Gender, dan Lingkungan Kampus Terhadap Persepsi Etis Mahasiswa Akuntansi Universitas 17 Agustus 1945 Surabaya - Miqdamuntaqo Ferdiansa; Tries Ellia Sandari (Journal of Economic and Business Advancement, 2026)
This research investigates how three factors business ethics instruction, gender differences, and the campus setting, shape the ethical views of accounting students at Universitas 17 Agustus 1945 Surabaya. A quantitative design was implemented using a survey with Likert‑type items administered to 37 accounting majors who had already completed the Business and Professional Ethics course. Instrument quality was evaluated through Pearson product-moment correlations and Cronbach’s Alpha, and the data were further analyzed using tests of normality, the coefficient of determination, and t and F statistics in a multiple linear regression model. The results show that both business ethics education and the campus environment exert a positive and statistically significant influence on students’ ethical judgments, while gender does not exert a significant effect. Taken together, these predictors account for a considerable share of the variability in ethical perceptions, highlighting the importance of reinforcing ethics‑oriented coursework and cultivating a campus climate grounded in integrity to prepare technically proficient and ethically responsible future accountants